Functional assignment of multiple ESCRT‐III homologs in cell division and budding in Sulfolobus islandicus - Liu, Junfeng; Gao, Renxia; Li, Chengtao; Ni, Jinfeng; Yang, Zhaojie; Zhang, Qi; Chen, Haining; Shen, Yulong (Molecular microbiology, 2017)
Summary The archaea Sulfolobus utilizes the ESCRT‐III‐based machinery for cell division. This machinery comprises three proteins: CdvA, Eukaryotic‐like ESCRT‐III and Vps4. In addition to ESCRT‐III, Sulfolobus cells also encode three other ESCRT‐III homologs termed ESCRT‐III‐1, −2 and −3. Herein, we show that ESCRT‐III‐1 and −2 in S. islandicus REY15A are localized at midcell between segregating chromosomes, indicating that both are involved in cell division. Genetic analysis reveals that escrt‐III‐2 is indispensable for cell viability and cells with reduced overall level of ESCRT‐III‐1 exhibit growth retardation and cytokinesis defect with chain‐like cell morphology. In contrast, escrt‐III‐3 is dispensable for cell division. We show that S. islandicus REY15A cells generate buds when infected with S. tengchongensis spindle shaped‐virus 2 (STSV2) or when ESCRT‐III‐3 is over‐expressed. Interestingly, Δescrt‐III‐3 cells infected with STSV2 do not produce buds. These results suggest that ESCRT‐III‐3 plays an important role in budding. In addition, cells over‐expressing the C‐terminal truncated mutants of ESCRT‐III, ESCRT‐III‐1 and ESCRT‐III‐2 are maintained predominantly at the early, late, and membrane abscission stages of cell division respectively, suggesting a crucial role of the ESCRTs at different stages of membrane ingression. Intriguingly, intercellular bridge and midbody‐like structures are observed in cells over‐expressing MIM2‐truncated mutant of ESCRT‐III‐2. Sulfolobus utilizes the ESCRT‐III‐based machinery for cell division. We show that, in addition to ESCRT‐III, ESCRT‐III‐1 and −2 in S. islandicus REY15A are also involved in cell division, while ESCRT‐III‐3 plays an important role in budding. ESCRT‐III, ESCRT‐III‐1 and −2 functions at different stages of membrane ingression. In addition, intercellular bridge and eukaryotic midbody‐like structures are observed in cells over‐expressing MIM2‐truncated mutant of ESCRT‐III‐2, suggesting a common mechanism of cell division in Sulfolobus and eukaryotes.